Coverage and accuracy of myeloproliferative and myelodysplastic neoplasms in the Finnish Cancer Registry. (2nd June 2016) - Leinonen, Maarit K; Rantanen, Matti; Pitkäniemi, Janne; Malila, Nea
Abstract: Background Registration of haematological malignancies presents specific challenges, and a wide range of data is required to ensure case ascertainment and proper classification of these diseases. We studied the data quality of myeloproliferative and myelodysplastic neoplasms in the Finnish Cancer Registry (FCR), comparing information with hospital discharges.Material and methods Hospital discharges (HILMO) in 2007–2013 including diagnostic codes of myeloproliferative and myelodysplastic neoplasms were extracted. Patients were individually linked to the FCR database for all haematological malignancies registered in 1953–2013. Coverage and accuracy of the FCR and agreement between registers was estimated.Results In total 5289 individuals were retrieved from two registers. Of these, 1406 were common, 1080 only found in the FCR and 2803 only in the HILMO. Coverage of myeloproliferative and myelodysplastic neoplasms in the FCR was 47.0% (95% CI 45.7–48.4%). Almost one quarter of the registrations in the FCR was based on a death certificate only. The accuracy of diagnosis was 51.4% (95% CI 49.4–53.3%), but it varied substantially by disease category. Kappa statistic for agreement between registers was excellent (0.83, 95% CI 0.80–0.85) for common cases. 7.6% of cases in the HILMO was registered as leukaemias in the FCR.Conclusions More than half of the patients found in the HILMO were entirely missing from the FCR. However, some of the diagnoses in HILMO may be preliminary and this represents the maximal number of missing cases. Cancer registers benefit from supplementary data sources, such as hospital discharges, to increase coverage and accuracy of register data on haematological malignancies.